Achieving Ultra‐Low Contact Resistance via Copper‐Intercalated Bilayer MoS2 - Huan Wang; Xiaojie Liu; Hui Wang; Yin Wang; Haitao Yin (Advanced Electronic Materials)
Abstract The high contact resistance between MoS2 and metals hinders its potential as an ideal solution for overcoming the short‐channel effect in silicon‐based FETs at sub‐3 nm scales. A MoS2‐based transistor, featuring bilayer MoS2 connected to Cu‐intercalated bilayer MoS2 electrodes is theoretically designed. At 0.6 V, contact resistance is 16.7 Ω µm (zigzag) and 30.0 Ω µm (armchair), nearing or even surpassing the 30 Ω µm quantum limit for single‐layer materials. This low resistance is attributed to the elimination of the tunneling barrier and the creation of ohmic contacts. Additionally, the small contact potential difference enables lower operating voltages. The intercalation design offers a novel approach to achieving low contact resistance in two‐dimentional electronic devices.